Outside the gate: sub-urban legal practices in early medieval England - Baker, John; Brookes, Stuart (Taylor and Francis, 2013)
Many aspects of English early medieval (Anglo-Saxon) legal landscapes can be discerned in archaeological and toponymic evidence, ranging from the locations of legislative councils and judicial assemblies to sites of capital punishment. Among the corpus of such sites a striking group can be detected at the periphery of urban spaces. Gates into a number of towns appear to have functioned as legislative meeting-places, and even gave their names to some legally constituted communities, while suburban locations also feature prominently as sites of gallows and public punishment. In this paper historical, archaeological and toponymic evidence is used to examine this phenomenon of suburban legal practices and to pose questions about the wider dimensions of the early medieval legal landscape.